Effect of Diaspora Remittances on Economic Development in Kenya - Issack, Fartun Adan; Nzai, Charles (International Journal of Economic Policy, 2023)
Purpose: This study intended to establish the effects of remittances from Kenyans residing abroad on the country's economic growth from 1988 to 2021. The study specifically calculated how diaspora remittances would affect the country's absolute poverty from 1988 to 2021, as well as how they would affect gross domestic product and gross national product. Methodology: The study implored the error correction model to conduct the estimation due to the stochastic nature of remittances. The modified Granger causality test by Toda and Yamamoto was applied to examine the connections between GDP and remittances as well as the connections between poverty and remittances. Using STATA software, an econometric estimation was performed. Findings: According to the study, remittances per capita had a significant impact on Kenya's GDP, GNI, and degree of absolute poverty. It was discovered that GDP and GNI per capita were granger causes of remittance per capita, but neither absolute poverty nor remittance per capita were granger caused by absolute poverty. Unique Contribution to Theory, Policy and Practice: The report recommends that, in order to guarantee a steady stream of remittances into the country's economy, essential efforts be taken to stabilize the currency rate and inflation.